Islamic education reform for new women leadership of the millennial generation - Ahmad H.Osman, Rahmah (2018)
Our globalized world is interconnected, interdependent and networked. Change can only be studied meaningfully in a transdisciplinary framework that takes account of the complex diversity of human societies and cultures and diverse disciplines of knowledge. We cannot have knowledge ‘once and for all’ but rather that knowledge is ‘something we have to actively feel our way around and through, unendingly.